TELAAH MAQASID SYARIAH TERHADAP PUTUSAN MK NO. 22/PUU-XV/2017 TENTANG BATAS USIA NIKAH - latief, hamzah (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2019)
AbstractThis study is a review of the decision of the Mahkamah Konstitusi (MK) No.22 / PUU-XV / 2017 about the age limit of marriage. The marriage age formulation carried out by the Mahkamah Konstitusi through recommendations in its decision to be revised up to the age of female marriage between 18-19 years. This study is a normative study with a library analysis of the Mahkamah Konstitusi decision regarding the age of marriage in the perspective of maqasid syari'ah. The results of the study indicate that the Mahkamah Konstitusi decision No.22 / PUU-XV / 2017 regarding changes in the age of marriage for women is in line with the concept of maqasid syari'ah. Keywords: MK Decision; Age of Marriage; Maqasid Syari'ah.